URGENSITAS PENDEKATAN PSIKOLOGI DALAM PELAKSANAAN MEDIASI DI PENGADILAN - Asnawi, M Natsir (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
The court mediation tends to ignore psychological aspect of the parties. It was frequently put aside by mediator judges as the mediation held just for formality process. It caused the lack percentage of successful mediation and the parties failed to recognize the primary problem. The research’s aim was to analyze the importance of implementation psychological approach to court-annexed mediation and its implication to the result of the mediation process. The research also aims to identify the implication of psychological approach toward parties’ perspective of their dispute. The result of the research has shown that implementation of psychological approach through mediation has arisen the probability of successful mediation. If otherwise happened, the parties have a broader perspective on their problem and released a new constructive way of thinking.Keywords: mediation, court, psychology, perspective